PENGARUH GERAKAN LITERASI SEKOLAH DAN RASA PERCAYA DIRI TERHADAP PRESTASI BELAJAR SISWA DI SMK NEGERI 1 KARANGANYAR - Aime Ashianti Fathonah; Hery Sawiji; Anton Subarno (JIKAP (Jurnal Informasi dan Komunikasi Administrasi Perkantoran), 2019)
The research aims to determine: 1) the effect of the school literacy movement on student achievement at Vocational High School 1 Karanganyar; 2) the effect of self-confidence on student learning achievement at Vocational High School 1 Karanganyar; 3) the effect of the school literacy movement and self-confidence simultaneously on student achievement at Vocational High School 1 Karanganyar. This research is a quantitative study with a correlational description method. The population of this study was all students of grade XI the Office Management Automation department at Vocational High School 1 Karanganyar. The sample technique used a total sampling as many as 72 students. Data were collected using questionnaires and documents. The data were analyzed using multiple regression (sign 0,05). The results of the study show that 1) there is a positive and significant effect of school literacy movement on student learning achievement indicated tcount > ttable (2,06 > 1,99); 2) there is a positive and significant effect of self-confidence on student learning achievement indicated tcount > ttable (4,25> 1,99); 3) there is a positive and significant effect of the school literacy movement and self-confidence simultaneously on student learning achievement indicated Fcount > Ftable (15,61> 3,13) and the determinant (R2) is 0,31 or 31%. Based on the findings, it could be suggested  that the school could provide information regarding the importance of reading and stimulate students continually in increasing self-confidence.